Productivity growth in European railways: technological progress, efficiency change and scale effects - Heike Wetzel (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2008)
This paper analyzes the performance of the European railway sector in the period of deregulation (1990-2005). Using a stochastic frontier panel data model that controls for unobserved heterogeneity a multiple-output multipleinput distance function model is estimated in order to evaluate the sources of productivity growth: technological progress, technical efficiency change and scale effects. The results indicate that technology improvements were by far the most important driver of productivity growth, followed by gains in technical efficiency, and to a lesser extent by exploitation of scale economies. Overall, we find an average productivity growth of 39 per cent within the sample period.
Keywords: D24; L51; L92; 330; European railways; deregulation; stochastic frontier analysis; total factor productivity